Protoplast formation and regeneration of a thermophilic Clostridium sp. - Julia Pettinari, M. (1989)
Protoplasts of a thermophilic Clostridium sp. were prepared by lysozyme treatment using lactose as osmotic stabilizer. High frequency reversion (3-29.8%) to the bacillary form was obtained on hypertonic rich medium. © 1989.